Interim report on the senior scholars Journal Basket review senior scholar's forum - Currie, W.; Dennis, A.; Nickerson, R.; Niederman, F.; Vogel, D.; Baskerville, Richard (2016)
To date, panel members have presented this material at PACIS and AMCIS. These presentations have triggered much discussion with many participants adding detailed comments and reasoning to viewpoints presented. It is clear that the role of the Basket of 8 is complex, affects different stakeholders within the AIS community in different ways, and has implications for evaluation and promotion criteria for IS faculty. It also affects to some degree the nature and content of research undertaken and the publication process. The panel will continue exploring these issues at the ICIS senior scholars' forum.